The analysis of Slovenian political party programs regarding doctors and health workers from 1992 to 2014 - Maksuti, Alem (Zdravstveno varstvo, 2016)
Introduction. The study focuses on the programmatic bases of Slovenian political parties since independence. It presents an analysis of party programs and their preferences regarding doctors and other health workers, as well as the contents most commonly related to them. At the same time, the study also highlights the intensity of the presence of doctors on the policy agenda through time. Methods. In the study, 83 program documents of political parties have been analysed. The study includes programmes of political parties that have occurred in parliamentary elections in Slovenia between 1992 and 2014 and have exceeded the parliamentary threshold. The data were analysed using the content analysis method, which is suitable for analysing policy texts. The analysis was performed using ATLAS.ti, the premier software tool for qualitative data analysis. Results. The results showed that doctors and other health workers are an important political topic in noncrisis periods. At that time, the parties in the context of doctors mostly dealt with efficiency and the quality of services in the health system. They often criticize doctors and expose the need for their control. In times of economic crisis, doctors and other health workers are less important in normative commitments of parties. Conclusions. Slovenian political parties and their platforms cannot be distinguished ideologically, but primarily on the principle of access to government. It seems reasonable to conclude that parties do not engage in dialogue with doctors, and perceive the latter aspassive recipients of government decisions-politics.
Keywords: Physicians; Political parties; political party; Political programs; Politične stranke; Politični programi; Slovenia; Slovenija; Zdravniki